Sputter-Deposited Binder-Free Nanopyramidal Cr/γ-Mo2N TFEs for High-Performance Supercapacitors - Durai Govindarajan; Nithyadharseni Palaniyandy; Karthik Kumar Chinnakutti; Mai Thanh Nguyen; Tetsu Yonezawa; Jiaqian Qin; Soorathep Kheawhom (Nanoscale Research Letters, 2022)
Abstract Due to their outstanding power density, long cycle life and low cost, supercapacitors have gained much interest. As for supercapacitor electrodes, molybdenum nitrides show promising potential. Molybdenum nitrides, however, are mainly prepared as nanopowders via a chemical route and require binders for the manufacture of electrodes. Such electrodes can impair the performance of supercapacitors. Herein, binder-free chromium (Cr)-doped molybdenum nitride (Mo2N) TFEs having different Cr concentrations are prepared via a reactive co-sputtering technique. The Cr-doped Mo2N films prepared have a cubic phase structure of γ-Mo2N with a minor shift in the (111) plane. While un-doped Mo2N films exhibit a spherical morphology, Cr-doped Mo2N films demonstrate a clear pyramid-like surface morphology. The developed Cr-doped Mo2N films contain 0–7.9 at.% of Cr in Mo2N lattice. A supercapacitor using a Cr-doped Mo2N electrode having the highest concentration of Cr reveals maximum areal capacity of 2780 mC/cm2, which is much higher than that of an un-doped Mo2N electrode (110 mC/cm2). Furthermore, the Cr-doped Mo2N electrode demonstrates excellent cycling stability, achieving ~ 94.6% capacity retention for about 2000 cycles. The reactive co-sputtering proves to be a suitable technique for fabrication of binder-free TFEs for high-performance energy storage device applications. Graphical Abstract